Histopathological spectrum of papillary carcinoma thyroid – a 4 year retrospective analysis - Dr. Anupama Raj K; Dr. Benzy Paul; Dr. K A Aisabi (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Papillary carcinoma of thyroid is the most common malignant tumor constituting about 80% of all malignancies of thyroid. It has an indolent course with an excellent prognosis and numerous histological variants have been reported till date. Also various associated lesions are also being noted, of which has himotos thyroiditis is one of the common lesions.Objective: 1) To analyse various histopathological features of papillary carcinoma thyroid. 2) To evaluate the presence or absence of has himotos thyroiditis in the background of papillary carcinoma.Design: Hospital based cross sectional study. Subject: Histopathologically diagnosed cases of papillary carcinoma thyroid in a 4 year period.Methods: Retrospective analysis of histopathologically diagnosed cases of papillary carcinoma thyroidhas been done. Results: Papillary carcinoma thyroid is more prevalent among females with most of the lesions showing conventional papillary pattern in 72.8% cases. Almost all the cases have the typical nuclear features described. Hashimotos thyroiditis is seen in 44.2% of the cases. Papillary micro carcinoma seen in 17.1% patients. Multi focality is seen in 28.5%. The association between papillary carcinoma and has himotos thyroiditis was evaluated using chi square test, p value= 0.001 and was found to be statistically significant.Conclusion: Our study has well correlated with the literature, with regards to epidemiological profile and the predominant histopathological pattern. Hashimotos thyroiditis is predominant associated lesion.